2019
DOI: 10.1108/er-04-2018-0100
|View full text |Cite
|
Sign up to set email alerts
|

Employee involvement and job satisfaction: a tale of the millennial generation

Abstract: Purpose The purpose of this paper is to empirically study the effect of employee involvement in the workplace on job satisfaction for millennial workers in Colombia. Design/methodology/approach Data were obtained from a sample of 2103 millennial employees working in 11 companies of different sectors located in the five main cities of Colombia. Ordered probit models were estimated to study the effect of employee involvement on job satisfaction, in general, and how different forms of participative decision mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 48 publications
(57 reference statements)
4
58
0
5
Order By: Relevance
“…Likewise, the study reinforces the conclusions of Meleiro and Siqueira (2005), Sant'Anna, Paschoal and Gosendo (2012), Seidl and Tróccoli (2006) that the relationship with management is a variable that substantially influences motivation, nurturing the well-being of employees. Briefly put, the results follow trends identified in Latin American studies on the expectations and characteristics of the work sought by Generation Y (Zavala-Villalón & Frías Castro, 2018;Silva et al, 2015;Twenge & Campbell, 2012;García et al, 2019;Veloso et al, 2016;Reis & Braga, 2016), the influence of organizational support (Madero-Gómez & Olivas-Luján, 2016) and the influence of leader relationships on Generation Y employee motivation (Hannus, 2016;Allen, 2005). The additional contribution of this study was to show how manager support moderates this relationship between organizational support and intrinsic motivation.…”
Section: Analysis Of the Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Likewise, the study reinforces the conclusions of Meleiro and Siqueira (2005), Sant'Anna, Paschoal and Gosendo (2012), Seidl and Tróccoli (2006) that the relationship with management is a variable that substantially influences motivation, nurturing the well-being of employees. Briefly put, the results follow trends identified in Latin American studies on the expectations and characteristics of the work sought by Generation Y (Zavala-Villalón & Frías Castro, 2018;Silva et al, 2015;Twenge & Campbell, 2012;García et al, 2019;Veloso et al, 2016;Reis & Braga, 2016), the influence of organizational support (Madero-Gómez & Olivas-Luján, 2016) and the influence of leader relationships on Generation Y employee motivation (Hannus, 2016;Allen, 2005). The additional contribution of this study was to show how manager support moderates this relationship between organizational support and intrinsic motivation.…”
Section: Analysis Of the Resultssupporting
confidence: 65%
“…The theory of exchange between leader and employee (known as Leader-member exchange or LMX) suggests that several elements may eventually influence employees' behavior, motivation and actions, including the manager's way of leading, and resulting in the type of relationship established between the manager and the employee (de Oliveira & da Costa Rocha, 2017). Furthermore, for workers of Generation Y, there is a positive relationship between engagement and job satisfaction, as well as a greater positive impact on satisfaction when they participate in decisions about general aspects of the company (García et al, 2019).…”
Section: Leader-member Exchange (Lmx)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the related research, millennial employees share similar social and historical contexts, are more ambitious and concerned about career development, desire empowerment and autonomy at work, highlight quality of life, and value work-life balance and overall well-being [18,19,38]. Chen and Choi (2008) found that millennial employees in hospitality emphasize comfort and security, and professional growth work values [43].…”
Section: Millennial Employee Well-being In Hospitalitymentioning
confidence: 99%
“…Diego René Gonzales-Miranda * La proliferación de literatura sobre la generación Y o millennials expresa la importancia y el interés del sector empresarial y del mundo académico por estudiar y comprender esta generación tanto en el ámbito social como en el organizacional. Mucha de esta información evoca reflexiones sobre sus características, su inserción en el mercado como empleados, consumidores e inversionistas (Kempf Taylor, 2018), por los factores que los motivan (Wong, Gardiner, Lang & Coulon, 2008), por la satisfacción en su lugar de trabajo (García Cruz, Gonzales-Miranda, Gallo & Román Calderón, 2019), entre otros muchos aspectos. Esto es comprensible ya que los millennials se convierten hoy en día en la generación que tiene bajo su responsabilidad gran parte de los procesos productivos y de servicios en las organizaciones, a la par que comienzan a ocupar puestos de responsabilidad en la alta dirección de estas.…”
Section: Mitos Y Realidades De Los Millennials Colombianosunclassified